Barriers to and Enablers of Usability in Electronic Consumer Product Development: A Multiple Case Study. (2nd January 2017) - van Kuijk, Jasper; Kanis, Heimrich; Christiaans, Henri; van Eijk, Daan
Abstract : This study identified practitioner-reported barriers to and enablers of usability in the development of electronic consumer products. Barriers and enablers are properties, situations, or conditions in the product development process, team, or context that negatively or positively influence the usability of a product. Based on a review of literature on user-centered design and exploratory expert interview, central concepts for studying usability in practice were identified. This was used as input for the case study, which was conducted at 5 product development groups in large multinationals, making (a) portable audio/video players, (b) personal navigation devices, (c) cell phones, (d) laundry care products, and (e) home control products. Data were primarily collected through interviews with 31 product development practitioners. Based on the data collected, case descriptions were created and more than 1, 500 barriers and enablers were identified, categorized, and analyzed. The results of the study are 23 sets of barriers and enablers, of which it is indicated in which of the cases they occur, and accompanied with illustrative quotations from the interviewees. In barriers and enablers, a predominantly "outside–in" relation was observed, from the more external properties of companies (market, company organization) to the more internal (process, team, project). This seems to indicate that the user-centeredness of a product development process is highly influenced by the context in which it is executed. The results also lead to the conclusion that if the goal is to make usable products, one cannot only address activities that are generally considered typical of user-centered design, such as conducting user research and user testing. One also has to take into account how these activities are integrated with and supported by the rest of the product development process, which in turn has to be supported by the product development organization.